Development of Natural Language Processing (NLP) Solution for Text Summarization from Web-pages - Leow, Kar Yee; Jawad, Mohammed Saeed (Applied Information Technology And Computer Science, 2023)
Text summarization system using Natural Language Processing (NLP) solution was developed to handles problems faced by students. There are several problems that students faced without text summarization, such as students require to summarize texts to help them complete their assignments or projects, need to manually summarize text from web-pages, and difficult to memorise excessive number of articles. The objectives of this project are to analyse and design a text summarization system based on structured approach, develop a text summarization system using an NLP solution and evaluate the developed system. The prototype model is used in this project. This system is expected to store the records of students and summary results, and the students summarize texts, view summary history records, and generate summary report through this system. Therefore, this system can improve the effectiveness of text summarization in a quick way.